Dietary Caprylic Acid (C8:0) Does Not Increase Plasma Acylated Ghrelin but Decreases Plasma Unacylated Ghrelin in the Rat - Lemarié, Fanny; Beauchamp, Erwan; Dayot, Stéphanie; Duby, Cécile; Legrand, Philippe; Rioux, Vincent (PLOS ONE, 2015)
Focusing on the caprylic acid (C8:0), this study aimed at investigating the discrepancy between the formerly described beneficial effects of dietary medium chain fatty acids on body weight loss and the C8:0 newly reported effect on food intake via ghrelin octanoylation. During 6 weeks, Sprague-Dawley male rats were fed with three dietary C8:0 levels (0, 8 and 21% of fatty acids) in three experimental conditions (moderate fat, caloric restriction and high fat). A specific dose-response enrichment of the stomach tissue C8:0 was observed as a function of dietary C8:0, supporting the hypothesis of an early preduodenal hydrolysis of medium chain triglycerides and a direct absorption at the gastric level. However, the octanoylated ghrelin concentration in the plasma was unchanged in spite of the increased C8:0 availability. A reproducible decrease in the plasma concentration of unacylated ghrelin was observed, which was consistent with a decrease in the stomach preproghrelin mRNA and stomach ghrelin expression. The concomitant decrease of the plasma unacylated ghrelin and the stability of its acylated form resulted in a significant increase in the acylated/total ghrelin ratio which had no effect on body weight gain or total dietary consumption. This enhanced ratio measured in rats consuming C8:0 was however suspected to increase (i) growth hormone (GH) secretion as an increase in the GH-dependent mRNA expression of the insulin like growth Factor 1 (IGF-1) was measured (ii) adipocyte diameters in subcutaneous adipose tissue without an increase in the fat pad mass. Altogether, these results show that daily feeding with diets containing C8:0 increased the C8:0 level in the stomach more than all the other tissues, affecting the acylated/total ghrelin plasma ratio by decreasing the concentration of circulating unacylated ghrelin. However, these modifications were not associated with increased body weight or food consumption.